Plants diversity of the deforested peat-swamp forest of Tripa, Indonesia - DJUFRI DJUFRI; WARDIAH WARDIAH (Biodiversitas Journal of Biological Diversity, 2016)
Djufri, Wardiah, Muchlisin ZA. 2016. Plants diversity of the deforested peat-swamp forest of Tripa, Indonesia. Biodiversitas 17: 372-376. Tripa peat swamp forest has been degraded due to human perturbation and resulted in decreasing the plant diversity.Currently, no report on plant diversity from this region in another hand the degradation is occurring continuously. Hence, the purpose ofthe present study was to evaluate the plants diversity of the Tripa peat swamp forest in Aceh Barat District, Indonesia. A quadraticmethod was employed in this study. Determination of the square area was carried out based on the curve of minimum area. The resultshowed that there were 41 species of herbs with diversity index ranging from 1.8785 to 2.4180 classified as low to moderate categories.A total of seven species of shrubs and 24 species of trees were found at the locations with diversity index (H') ranging from 1.5186 to 1.7496 and 2.1713 to 2.9133 respectively, indicating the diversity of shrubs was in a low category, while the diversity of tress was in the moderate level. It is concluded that the diversity index of herbs and shrubs were in a low category while the tree groups were in the medium category. According to the diversity index and direct observation of the Tripa peat swamp forest, this area had been degraded due to land conversion.